A comparative study on immune responses to demineralized and decellularized bone substitute following intraperitoneal implantation in mouse model - K. G. Aghila Rani; Ali Al Qabbani; Sausan AlKawas; Manju Nidagodu Jayakumar; S. A. H. Suzina; A. R. Samsudin; Ahmad Azlina (PLoS ONE, 2025)
The immunological sensitization of implanted bone grafts is crucial for long-term success. This study aimed to investigate the immune responses following implantation of lyophilized demineralized (DMB) and lyophilized decellularized (DCC) bovine cancellous bone substitutes, respectively, in mouse models of peritoneal implantation to evaluate the effectiveness of DMB and DCC processing methods. The DMB and DCC substitutes were prepared using published methods. BALB/c mice were divided into four groups (n = 4). A small abdominal incision was created to deliver the DMB or DCC materials into the peritoneal cavity. The first group received native unprocessed bone, while the second group was sham-operated (SO). The third and fourth groups received DMB and DCC substitutes, respectively. The immunogenicity effects of the implants were assessed through WBC count, spleen index, CD4 + /CD8 + counts, cytokine expression, and histology analysis of the spleen, liver and kidney. Native controls displayed systemic inflammation. The DMB group showed an increased trend in WBC count, cytokine profile and spleen index on day seven, followed by a considerable reduction in the DCC group compared to DMB on days 14 and 21. The native group showed significantly higher CD4+ /CD8+  T-cells and proinflammatory cytokines (IL-12, TNF-α, IFN-γ, MCP-1, IL-6). Additionally, the DMB group showed significantly higher mRNA levels for IL-1β, TNF-α, IL-6, and the anti-inflammatory cytokine IL-10. The DMB group further exhibited a significantly higher CD4 +  count, while the DCC group demonstrated higher CD8+  T-cells on day 1. Histological assessments of the liver and kidney revealed pyknotic nuclei, necrotic cells, and extravasated RBCs in the native group and, to a lesser extent, in the DMB group, while the DCC group showed normal morphology similar to Sham. Both DMB and DCC demonstrated favourable immunocompatibility properties, while DCC exhibited further immune tolerance in the mouse model.